Elite or grassroots? A feminist institutionalist examination of the role equalities organisations play in delivering representation and participation in a third sector–government partnership. (2nd March 2022) - Sanders, Amy
Abstract : This study examines institutional discourses about representation and participation in the Welsh third sector–government partnership. It applies a feminist institutionalist lens to understand how the representation of equalities third sector organisations is enabled and constrained. The theoretical foundation brings together diverging literatures on third sector–state relations, democracy theory and understandings of descriptive representation in the equalities literature. Using semi-structured elite interviews, it employs critical discourse analysis to scrutinise policy actors' partnership accounts. Findings reveal how equalities representation is restricted by institutional expectations for the third sector's unified voice. Furthermore, institutionalist discourses about the the 'usual suspects' and scrutiny of the grassroot–professional paradox reveal how Welsh equalities representation is under threat. This analysis reveals the complex interaction of diverging uses of representation and participation that serve to undermine the legitimacy of expert knowledge on inequalities to inform state policy making in favour of populist constructions of the wider citizen voice.